Simulation of radiation conditions in contaminated rooms - Batiy, V.G.; Fedorchenko, D.V. (Вопросы атомной науки и техники, 2007)
Method for beta and gamma radiation exposure rate calculations inside the radioactively contaminated buildings is presented. Method is based on the realistic model accounting for removable and irremovable components of the surface contamination. Exposure rate calculations for areas with considerable level of surface contamination are presented and discussed. Представлено метод розрахунку потужності дози бета- та гамма-випромінювань всередині забруднених приміщень. Створений метод оснований на реалістичній моделі, який враховує поверхневе забруднення, що знімається та таке, що не знімається. Наведено результати розрахунків для сильно забруднених приміщень об'єкту "Укриття". Представлен метод расчета мощности дозы бета- и гамма-излучений внутри загрязненных помещений. Разработанный метод основан на реалистичной модели с учетом снимаемой и неснимаемой составляющих поверхностного загрязнения. Приведены результаты расчетов для сильно загрязненных помещений объекта "Укрытие".